The Role of Technology: MOODLE as a Learning Tool and Its Impact on the Students’ Learning - Nabila Nilna Ghina; Mutmainnah Mustofa; Muzayyanah Awaliyah (Universitas Lancang Kuning, 2022)
This research aims to determine students' perceptions and attitudes towards the use of MOODLE as a learning tool. The data sources for this study were 17 postgraduate students in English Education, UNISMA. To collect data, researchers have distributed questionnaires via google form and the data obtained were analyzed using SPSS 2.0. The results show that students have a tendency to have a positive view of the use of MOODLE as a learning tool. This tendency also leads to the results of the investigation of students' attitudes. Students show a sense of liking and comfortable using MOODLE. This positive attitude increased as their familiarity with the Moodle app increased and their ability to organize their own learning.